Social Entrepreneurship and Social Innovation: A Bibliometric Analysis - Valadez-Solana, Brenda Dennís; Cruz-Cabrera, Blasa Celerina; Huesca-Gastélum, Martín Isimayrt; Castillo-Leal, Maricela (Unidad Editorial UPTC, 2023)
There is a growing academic interest in social entrepreneurship (SE) and social innovation (SI) due to its importance in influencing the development of regions. The objective of the study is to carry out a bibliometric review of the existing literature on SE and IS through a quantitative integrative vision. A bibliometric analysis was carried out in the period 1989-2022 with information obtained from the Scopus database. 475 publications were reviewed using the performance analysis and scientific cartography methods. In the performance analysis, the h-index, citation threshold, and temporality dimensions were used as indicators. In scientific cartography, co-citation and co-occurrence techniques were applied, and network maps were created using the Vosviewer® software. The results showed that the United Kingdom is the country with the highest productivity and influence in the field of SE and SI. The most representative authors were Tina Dacin, Peter Dacin, Paul Tracey, Gregory Dees, Patrick Dawson, and Lisa Daniel. The social enterprise, corporate social responsibility and social capital are issues closely linked to SE and SI. Future trends will be aligned with the approaches to sustainability and its impact on the development of the regions, oriented towards theoretical and practical considerations in which individuals manage to cooperate to achieve social goals. JEL Codes: O31, Y10, Z00 Received: 15/04/2023.  Accepted: 01/06/2023.  Published: 05/07/2023.